2012
DOI: 10.1007/s13538-012-0082-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Environmental Disturbances on Tumor Growth

Abstract: In this study, the analytic expressions of the steady probability distribution of tumor cells were established based on the steady state solution to the corresponding Fokker-Planck equation. Then, the effects of two uncorrelated white noises on tumor cell growth were investigated. It was found that the predation rate plays the main role in determining whether or not the noise is favorable for tumor growth.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…One motivation for the development of this model was to propose a mathematical framework within which we can understand resistance to treatment under the Frank-Rosner paradigm of drug resistance [ 5 ]. While most previous work on tumor growth modeling [ 25 33 ] has largely focused on the deterministic growth of tumors for mean values, heterogeneity and variability are key factors in understanding the development of tumors [ 5 , 34 , 35 ]. It has been observed that cancerous cells have greater variability in growth rate than do normal cells [ 36 ], confirming that there is merit to the assumption that growth rate is driven by a random process.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…One motivation for the development of this model was to propose a mathematical framework within which we can understand resistance to treatment under the Frank-Rosner paradigm of drug resistance [ 5 ]. While most previous work on tumor growth modeling [ 25 33 ] has largely focused on the deterministic growth of tumors for mean values, heterogeneity and variability are key factors in understanding the development of tumors [ 5 , 34 , 35 ]. It has been observed that cancerous cells have greater variability in growth rate than do normal cells [ 36 ], confirming that there is merit to the assumption that growth rate is driven by a random process.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Many systems in nature or laboratories are nonlinear and involve stochastic processes due to intrinsic variability, heterogeneity, or uncertainty in a system [1][2][3][4][5][6][7][8]. An interesting consequence of the complex interaction in these nonlinear systems is the ability to self-regulate [1,2,9], leading to the formation of an attractor; a set of states, invariant under the dynamics, towards which neighboring trajectories asymptotically approach following the dynamical evolution.…”
Section: Introductionmentioning
confidence: 99%
“…This concept has been generalized to non-equilibrium systems [36][37][38][39][40][41][42][43], including the utilization for controlling systems to minimize entropy production [38,40,42], the measurement of the statistical distance in experiments to validate theoretical predictions [41], etc. However, some of these works rely on the equilibrium distribution Equation (2) that is valid only in or near equilibrium while many important phenomena in nature and laboratories are often far from equilibrium with strong fluctuations, variability, heterogeneity, or stochasticity [44][45][46][47][48][49][50][51][52]. Far from equilibrium, there is no (infinite-capacity) heat bath that can maintain the system at a certain temperature, or constant fluctuation level.…”
Section: Introductionmentioning
confidence: 99%